Sport concussion education and prevention - Tator, C. H. (Journal of Clinical Sport Psychology, 2012)
There has been a remarkable increase in the past 10 years in the awareness of concussion in the sports and recreation communities. Just as sport participants, their families, coaches, trainers, and sports organizations now know more about concussions, health care professionals are also better prepared to diagnose and manage concussions. As has been stated in the formal articles in this special issue on sport-related concussion, education about concussion is one of the most important aspects of concussion prevention, with the others being data collection, program evaluation, improved engineering, and introduction and enforcement of rules. Unfortunately, the incidence of concussion appears to be rising in many sports and thus, additional sports-specific strategies are required to reduce the incidence, short-term effects, and long term consequences of concussion. Enhanced educational strategies are required to ensure that individual participants, sports organizations, and health care professionals recognize concussions and manage them proficiently according to internationally recognized guidelines. Therefore, this paper serves as a "brief report" on a few important aspects of concussion education and prevention.